Study of Potential Vinasse Compost as Fertilizer and Application on Cocoa (Theobroma Cacao L.) Seedlings - Galuh Banowati (Jurnal Agrivet, 2017)
This study aims to identify the content of macro nutrients vinasse compost, and the effect of application on the growth of cocoa seedlings. The study was conducted in Politeknik LPP greenhouse, from June to October 2016. The study was preceded by composting vinasse, then applied as fertilizer on cocoa seedlings. The design used was CRD, both to compare fresh vinasse with 10, 20, and 30 days composting, as well as comparing application with NPK and Organic Liquid Fertilizer. Compost application were splashed on the ground and sprayed to the leaves. Nutrient content were observed: organic matter, N, P, K, and pH. Growth parameters measured were: increases height diameter of the trunk. Data were analyzed using ANOVA 95%. The results showed the total N increased significantly in compost 10 days, organic matter and P decreased significantly, and K, pH increased significantly with increasing days of composting. No difference height and diameter of the trunk at all treatment applications. It was concluded that the compost vinasse potential as liquid fertilizer enhancer Potassium and serves as ameliorantKeywords: vinasse compost, cacao seedling